Physical activity before and during the COVID-19 pandemic in Vojvodina, Serbia - Jelena Obradović; Nikola Radulović; Duško Cvijović; Mila Vukadinović Jurišić (Frontiers Media S.A., 2022)
BackgroundThe physical activity (PA) of the youth and adult population underwent changes during the last 2 years due to the coronavirus (COVID-19) pandemic, and all for the purpose of maintaining the health of the population. The purpose of this study was to estimate the levels of PA in the youth population and the adult population (young and old) during the COVID-19 pandemic in the territory of Vojvodina, Serbia, and to determine the differences between them, as well as to compare these results with the results before the pandemic.MethodsA total of 1,117 subjects (age 36.27 ± 15.08 years) from the territory of Vojvodina, Serbia, participated in the study. Subjects were recruited and assigned to one of the three groups according to their age: youth group (N = 395; age 18-24 years), young adults group (N = 347; from 25 to 44 years), and old adults group (N = 375; age 45-65 years). All participants in this study completed the International Physical Activity Questionnaire Short-Form between July and November 2021, during the fourth wave of the COVID-19 pandemic in Vojvodina, Serbia. The Kruskal-Wallis test and Dunn multiple comparison post-hoc method were used for statistical analyses.ResultsThe youth showed the highest result in total weekly energy expenditure (3,893.72 ± 2,010.01 MET-min/week) compared to young adults (2,528.20 ± 1,804.11 MET-min/week) and old adults (2,369.07 ± 2,084.95 MET-min/week) during the COVID-19 pandemic in Vojvodina, Serbia. In addition, adults (young and old) spent more time sitting than youth during the same period. Furthermore, the youth achieved greater results in levels of PA during the COVID-19 pandemic compared to the situation before the COVID-19 pandemic. However, adult populations achieved lower results during the COVID-19 pandemic than before the COVID-19 pandemic.ConclusionDuring the COVID-19 pandemic, the youth from Vojovida, Serbia, achieved greater results in PA levels than the adult populations. Based on that, we recommend that it is necessary to take steps toward increasing PA in the adult population, especially old adults.